Kerk en skoolonderwys in vier kerkordes - P. J. Strauss (Acta Theologica)
Reformed churches in the tradition of John Calvin and the well-known Synod of Dordt (1618-1619), have a long history of involvement of some kind in school education. This article looks into the famous – at least in some circles – church order of Dordt, and the present orders of three reformed churches: the Reformed Churches in South Africa, the Dutch Reformed Church and the Christian Reformed Church in North America. All three tend to be in the tradition of Dordt. In the Dutch society of the 17th century close ties between the Reformed Church and the government gave this church the opportunity to influence Dutch school education. Firstly the church used the angle of the all embracing kingdom of God in which church and school are different institutes in society but serve the same Lord. Secondly the Reformed Church also influenced school education from the viewpoint of the church as church by introducing its confessions as a point of departure and also it’s discipline in schools. The other three churches opted for a say in the spiritual direction in schools, but not to tie them to a specific church. They strive for Christian and not church schools.